31 Ischaemia and viability assessment with adenosine stress cmr in high risk patients: safety, feasibility and tolerability. (26th April 2015) - Wilson, Catherine; Carpenter, Alexander; Dastidar, Amardeep Ghosh; Rodrigues, Jonathan; Ahmed, Nauman; Baritussio, Anna; Lawton, Chris Benny; McAlindon, Elisa; Bucciarelli-Ducci, Chiara
Abstract : Background: Adenosine stress cardiovascular magnetic resonance (CMR) provides effective cardiac prognostication in patients with suspected coronary artery disease. However its use has been limited in high-risk patients and some reservations exist about offering adenosine stress CMR in patients with significant aortic stenosis, asthma, severe left ventricular (LV) systolic dysfunction, significant left main stem (LMS) disease and age >80 years. Aims: To determine the safety, tolerability and feasibility of adenosine stress CMR, in high-risk individuals. Method: Consecutive adenosine stress-CMR examinations (March 2013–March 2014) were included. A comprehensive adenosine stress CMR protocol was used. High-risk if: age >80 years, asthma, significant LMS stenosis and moderate-severe or severe aortic stenosis or severe LV systolic dysfunction (ejection fraction <40%). Fisher exact test for binary variables was used. Results: 574 consecutive stress-CMR were included in the analysis (mean age 64 years and 71% males), out of which 128 patients (22%) met the criteria for high-risk. Overall, the complete stress-CMR protocol was successfully performed in 93% of patients: the high-risk group had a drop out rate of 2% compared to a rate of 7% for the non-high risk group (p = 0.08). Adequate stress response (symptomatic and/or cardiovascular) was achieved in 98% of high-risk and 97% of non-high risk (p = 0.55). 70% of high-risk patients received incremental increases in adenosine dose. Overall, no serious adverse events were noted. When compared to non-high risk, the high-risk group more commonly presented with inducible perfusion defects (62% vs 42%, p = 0.0003) and LGE (74% vs 55%, p = 0.0006). Conclusion: Adenosine stress-CMR is a safe, well-tolerated and feasible investigational modality even in high-risk individuals (moderate/severe aortic stenosis, significant LMS stenosis, severe LV systolic dysfunction, asthma/COPD or age >80) with known or suspected ischaemic heart disease. The incidence of myocardial ischemia or LGE is significantly higher in the high-risk group.